Costless discrimination and unequal achievements in a labour market experiment - Antonio Filippin; Francesco Guala (Institute for the Study of Labor (IZA), 2011)
We investigate the emergence of discrimination in an experiment where individuals affiliated to different groups compete for a monetary prize, submitting independent bids to an auctioneer. The auctioneer receives perfect information about the bids (i.e. there is no statistical discrimination), and she has no monetary incentive to favour the members of her own group (the bidders are symmetric). We observe nonetheless some discrimination by auctioneers, who tend to assign the prize more frequently to a member of their own group when two or more players put forward the highest bid. Out-group bidders react to this bias and reduce significantly their bids, causing an average decay of their earnings throughout the game, with cumulative effects that generate strongly unequal outcomes. Because the initial bias is costless, such mechanism can survive even in competitive market, providing a rationale for a well-known puzzle in the literature, i.e. the long-run persistence of discrimination.
urn:nbn:de:101:1-201201103667
Keywords: J71; D44; C9; 330; discrimination; tournament; groups; experiment; Diskriminierung; Extensives Spiel; Soziale Gruppe; Test; Auktionstheorie